Zion, ruhme Deinen Gott! Ein 'Zionisten' Fest in Norden Transvaals [Zion glorify thy God! A 'Zionist' Festival in N. Transvaal - Schneider, Theo (Schweizer Mission in Sudafrica, 1953)
On Edward Lekganyane's Zion Christian Church.